Semiotics Study of Structure and Meaning in Javanese Lullaby Song “Tak Lela-Lela Ledhung” - Dewi Herlina; Sulistyowati Sulistyowati (Haluan Sastra Budaya, 2025)
This study aims to describe the structure, semiotic meaning, and life values of Javanese people in lullaby songs. The data in this study is the text of a lullaby entitled Tak Lela-Lela Ledhung. The analysis is focused on the structure of the song Tak Lela-Lela Ledhung using the Halliday &Matthiessen theory. Semiotic analysis with Peirce's theory includes three aspects, namely sign, object, and interpretant. The representation of the value of life in the song is also presented to enrich the results of the analysis. The results of this study show that in the textual aspect, structural elements in Tembang Tak Lela-Lela Ledhung involve the use of inter-sentence relationships in the form of lexical cohesion and grammatical cohesion. Based on Peirce's semiotic analysis, the song Tak Lela-Lela Ledhung has a tendency to have constructions formed from the daily lives of Javanese people. In the lyrics of the song, advice is implied in the form of prayers and parents' hopes for their children's future. The values found are patience, hard work, and the will to fight for the future.